Case report: A disconjugate pattern in video head impulse testing hints toward a central cause of acute vertigo - Wettstein, Vincent G.; Feil, Bertram; Mono, Marie-Luise (Frontiers in Neurology, 2023)
When acute vertigo occurs, the challenge for the medical practitioner lies in the focused assessment to find the cause of its symptoms. Especially in case of a central pathology, a fast diagnosis is essential for therapy. The HINTS-protocol (Head impulse, Nystagmus, Test of Skew) and the additional video head impulse test (VHIT) can distinguish between central and peripheral vestibular causes in the acute setting and thus help to set the right path for further evaluation and treatment. In this case, a patient with acute onset of vertigo presented with an unusual pattern in the VHIT. Binocular eye tracking showed a disconjugate horizontal vestibulo-ocular reflex (VOR) with severe loss of gain for the adducting eye, yet a lack of corrective saccades. The abducting eye produced a pattern of mild VOR gain loss, yet pronounced corrective saccades. Together with clinical findings that were compatible with internuclear ophthalmoplegia, a probable central lesion in the medial longitudinal fasciculus (MLF) region was suspected. The patient was sent to a tertiary hospital, where the initial MRI was negative, but due to additional neurological symptoms occurring later, multiple lesions in the cervical spine and cerebellum where detected. The hypothesis of an inflammatory demyelinating disease of the central nervous system (CNS) was made. Further work-up lead to the final diagnosis of neurosarcoidosis. In a retrospective neuroradiologic assessment, an alteration compatible with a non-active demyelinating lesion in the MLF was detected on secondary imaging as a probable cause of the initial pathophysiologic finding. With this report, we want to highlight the unusual case of a disconjugate VOR as a distinctive VHIT pattern hinting towards a central cause of acute vertigo, that clinicians should be aware of.